2023
DOI: 10.1039/d2ta08095h
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interaction between Cu and sulfur vacancies in SnS2nanoflowers for highly efficient nitrate electroreduction to ammonia

Abstract: Achieving high efficiency in nitrate (NO3-) to ammonia (NH3) electrocatalysis requires the exploration of advanced electrocatalysts with a well-designed composition. In this work, a facile one-step hydrothermal method was applied...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Cu–SnS 2− x exhibited a significantly enhanced NO 3 RR activity with NH 3 yield (0.63 mmol h −1 mg cat −1 ) and FE NH3 (93.8%) at −0.7 V versus RHE. DFT calculations confirmed that V S causes the free electron transfer to Sn and introduction of Cu can further regulate the electron distribution leading to high NH 3 yield and FE NH3 173 . Wang et al.…”
Section: Electrocatalytic Nitrate Reduction To Nh3mentioning
confidence: 94%
See 1 more Smart Citation
“…Cu–SnS 2− x exhibited a significantly enhanced NO 3 RR activity with NH 3 yield (0.63 mmol h −1 mg cat −1 ) and FE NH3 (93.8%) at −0.7 V versus RHE. DFT calculations confirmed that V S causes the free electron transfer to Sn and introduction of Cu can further regulate the electron distribution leading to high NH 3 yield and FE NH3 173 . Wang et al.…”
Section: Electrocatalytic Nitrate Reduction To Nh3mentioning
confidence: 94%
“…By combining the strategies of V S and heteroatom doping, that Fe-doped SnS 2 nanosheet arrays grown on carbon cloth (Fe-SnS 2 /CC) developed as highly effective catalysts for NO 3 RR. Fe-SnS 2 /CC showed the NH 3 yield (7.2 mg h −1 cm −2 ) at to high NH 3 yield and FE NH3 173. Wang et al utilized a facile electrical Joule heating method to flexibly regulate the V S content on the surface of Ni 3 Co 6 S 8 (NCS-2), in which V S can regulate the electronic structure of NCS-2.…”
mentioning
confidence: 99%
“…The EPR spectra of pristine SnS 2 and Cu-doped SnS 2 have unveiled a distinctive and singular narrow signal, which is unmistakably characterized by a g-factor of 2.003 as shown in figure 4. This particular g-factor alignment is widely recognized as a hallmark signature of electrons trapped in sulfur vacancies within the material structure [59,60]. Intriguingly, when the SnS 2 samples are subjected to a 2 at% Cu doping, a remarkable augmentation in signal intensity becomes evident, particularly when juxtaposed with the undoped counterpart.…”
Section: Electron Paramagnetic Resonance Studiesmentioning
confidence: 95%
“…Additionally, Li et al. [ 205 ] synthesized Cu-doped SnS 2− x electrocatalysts via a hydrothermal method, which exhibited nearly twice the NH 3 yield (0.63 mmol h −1 mgcat −1 ) and FE (93.8%) compared to pristine SnS 2 at −0.7 V vs. RHE ( Fig. 9 g).…”
Section: Other Cu-based Composite Catalystsmentioning
confidence: 99%